Fatal denial: racism and the political life of black infant mortality - Menzel, Annie (Reproductive justice: a new vision for the twenty-first century, 2024)
"Fatal Denial argues that over the past 150 years, American health authorities' explanations of and interventions into Black infant mortality have been characterized by the "biopolitics of racial innocence," a term describing the institutionalized mechanisms in health care and policy that have at once obscured, enabled, and perpetuated systemic infanticide by blaming Black mothers and communities themselves. Following Black feminist scholarship demonstrating that the commodification and theft of Black women's reproductive bodies, labors, and care is foundational to US racial capitalism, Annie Menzel posits that the polity has inexorably produced Black infants' vulnerability to preventable death. Drawing on key Black political thought and praxis around infant mortality-from W.E.B. Du Bois and Mary Church Terrell to Black midwives and birth workers-this work also tracks continued refusals of this routinized reproductive violence, illuminating both a rich history of care and the possibility of more transformative futures"--